Antibacterial activities of moringa olifiera freeze dried extract on staphylococcus aureus - Wulan Angestia; Valendriyani Ningrum; Tai L. Lee; Shih-Chieh Lee; Abu Bakar (Journal of Dentomaxillofacial Science, 2020)
Objective: The aim of this study is to determine the antibacterial activities of M. oleifera freeze dried extract on Staphylococcus aureus. Material and Methods: The antibacterial activities using two methods, microdilution method and agar diffusion method. The minimum inhibitory concentration is determined. The measurement of absorbance in microdilution method using a spectrophotometer at length wave 590 nm. The inhibition zone is measured using scalimeter. Results: The results showed both microdilution method and agar diffusion method present the inhibition activity of M. oleifera freeze dried extract on staphylococcus aureus. Conclusion: The finding confirmed M. oleifera freeze dried extract as the promising antibacterial natural agent, particularly on inhibiting S. aureus strain.